2022
DOI: 10.1161/strokeaha.121.035846
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in the TST Trial

Abstract: Background and Purpose: Although statins are effective in secondary prevention of ischemic stroke, they are also associated with an increase risk of intracranial hemorrhage (ICH) in certain conditions. In the TST trial (Treat Stroke to Target), we prespecified an exploration of the predictors of incident ICH. Methods: Patients with ischemic stroke in the previous 3 months or transient ischemic attack within the previous 15 days and evidence of cerebrova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…Multiple studies have focused on the relationship between LDL-C and ICH, but their results have been inconsistent. Several prospective studies mainly in the field of CHD have demonstrated no significant association between them, 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 which were consistent with our results. Of notice, many of these studies were the prespecified analyses of well-known clinical randomized trials where ICH was evaluated as one of the safety endpoints (e.g., IMPROVE-IT, 27 FOURIER, 26 and SPARCL trials 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have focused on the relationship between LDL-C and ICH, but their results have been inconsistent. Several prospective studies mainly in the field of CHD have demonstrated no significant association between them, 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 which were consistent with our results. Of notice, many of these studies were the prespecified analyses of well-known clinical randomized trials where ICH was evaluated as one of the safety endpoints (e.g., IMPROVE-IT, 27 FOURIER, 26 and SPARCL trials 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this issue of Stroke, Amarenco et al 3 provide further reassurance that targeting lower levels of LDL following stroke and transient ischemic attack is a safe strategy. In the Treat Stroke to Target trial, patients were enrolled within 3 months of a stroke or transient ischemic attack (<15 days criterion for transient ischemic attack) if there was additional evidence of atherosclerotic disease.…”
Section: See Related Article P 457mentioning
confidence: 99%
“…Although the TST trial (Treat Stroke to Target) investigating a target LDL-C level of <70 mg/ dL (1.8 mmol/L; lower-target group) compared with a target range of 90 mg to 110 mg/dL (2.3-2.8 mmol/L; higher-target group), which excluded patients with a history of ICH and confined eligibility to patients with ischemic stroke/TIA and atherosclerotic disease, led to only a nonstatistically significant increased risk of ICH. 31,32 The TST trial was ended prematurely and may have had limited power to detect a difference in risk of ICH with only 33 events occurring during study follow-up relative to 88 ICH events in SPARCL.…”
Section: Hmg-co a Reductase Inhibitors (Statins)mentioning
confidence: 99%